Synthesis, Characterization and Evaluation of the Antimicrobial Activity of a New [1,2,4] Triazolo [3,4-B] [1,3,4] Thiadiazoles Derivatives - M. Juaila, Karrar; R. Jber, Nasreen (Al-Nahrain Journal of Science, 2024)
In this study, synthesis of [D-H] via reaction of compound [C] with p-alkoxybenzaldehyde. The derivative [C] that produces from reaction the 4-amino-5-(4-aminophenyl)-4H-1,2,4-triazole-3-thiol with phosphoryl chloride. The synthesized derivatives are characterized by 1HNMR and FTIR spectroscopies. The antibacterial activity of the obtained thiadiazol derivatives [D-H] was screened against Gram-positive bacteria viz. (Staphylococcus aureus, Bacillus subtilis) and Gram-negative bacteria viz. (Escherichia coli) by disc diffusion method, the results showed that compound [H] has the highest activity toward Bacillus subtilis and Staphylococcus aureus, while compounds [D] showed the highest activity toward E. coli.